Impact of anti-solar differential rotation in mean-field solar-type dynamos - Noraz, Q; Brun, A S; Strugarek, A; Depambour, G (Astronomy and astrophysics (Berlin), 2022)
Context. Over the course of their lifetimes, the rotation of solar-type stars goes through different phases. Once they reach the zero-age main sequence, their global rotation rate decreases during the main sequence until at least the solar age, approximately following the empirical Skumanich’s law and enabling gyrochronology. Older solar-type stars might then reach a point of transition when they stop braking, according to recent results of asteroseismology. Additionally, recent 3D numerical simulations of solar-type stars show that different regimes of differential rotation can be characterized with the Rossby number. In particular, anti-solar differential rotation (fast poles, slow equator) may exist for high Rossby number (slow rotators). If this regime occurs during the main sequence and, in general, for slow rotators, we may consider how magnetic generation through the dynamo process might be impacted. In particular, we consider whether slowly rotating stars are indeed subject to magnetic cycles. Aims. We aim to understand the magnetic field generation of solar-type stars possessing an anti-solar differential rotation and we focus on the possible existence of magnetic cycles in such stars. Methods. We modeled mean-field kinematic dynamos in solar (fast equator, slow poles) and anti-solar (slow equator, fast poles) differential rotation, using the STELEM code. We consider two types of mean field dynamo mechanisms along with the Ω-effect: the standard α-effect distributed at various locations in the convective envelope and the Babcock-Leighton effect. Results. We find that kinematic αΩ dynamos allow for the presence of magnetic cycles and global polarity reversals for both rotation regimes, but only if the α-effect is saddled on the tachocline. If it is distributed in the convection zone, solar-type cases still possess a cycle and anti-solar cases do not. Conversely, we have not found any possibility for sustaining a magnetic cycle with the traditional Babcock-Leighton flux-transport dynamos in the anti-solar differential rotation regime due to flux addition. Graphic interpretations are proposed in order to illustrate these cases. However, we find that hybrid models containing both prescriptions can still sustain local polarity reversals at some latitudes. Conclusions. We conclude that stars in the anti-solar differential rotation regime can sustain magnetic cycles only for very specific dynamo processes. The detection of a magnetic cycle for such a star would therefore be a particularly interesting constraint in working to decipher what type of dynamo is actually at work in solar-type stars.